Geopolitical Complexities of Kosovo: Symbolic and Geographical Tensions in the Western Balkans - Orsós, György (Modern Geográfia, 2025)
There is currently limited Hungarian-language scholarship on the geopolitical and political geographic issues of Kosovo. This study aims to fill this gap by identifying the most critical thematic areas based on international literature, thus presenting both Kosovo’s current issues and relevant research trends and approaches. Within the framework of classical geopolitics, the study outlines Kosovo’s position in the international sphere, noting that, despite the prominent roles of UNMIK and EULEX as central actors, Kosovo’s geopolitical interpretation remains complex and multifaceted. Additionally, it examines Kosovo’s regional relationships from a political geographic perspective, focusing on the ‚post-Westphalian system,’ ethnic geographic issues, and border-related questions. Given the broader political climate of the Western Balkans, the analysis of symbolic political conflicts is also essential; therefore, the study explores these dynamics, particularly through an overview of Kosovar and Albanian identity and the memory politics of Kosovopolje.